Quality of Nursing Care for Neonates with Respiratory Distress Syndrome at Neonatal Intensive Care Unit in Teaching Hospitals in Erbil City - Jihad Rasool Mamo; Norhan Zaki Shaker (Hawler Medical University, 2024)
Background and Objective: Quality of nursing care has an important role in providing the highest care to neonates in the neonatal intensive care unit. Improvement in the quality of nursing care is a main goal of the nurses. The study aimed to assess the quality of nursing care for neonates with Respiratory Distress Syndrome. Methods: A descriptive cross-sectional study was conducted on 50 nurses at neonatal intensive care units in teaching hospitals (Rapareen Teaching Hospital for Children and Maternity Teaching Hospital) in Erbil city. A convenience sampling technique was used to collect the data. Two tools were used to collect the data which was developed by the researcher: the first tool was a self-administered questionnaire which contained two parts (socio-demographic characteristics, and questions related to neonatal respiratory distress syn-drome), and the second tool was an observational checklist that was used to assess the quality of nursing care for NRDS. The Statistical Package for Social Science was used to analyze the data (version 23), presenting descriptive and inferential statistics, including the chi-square test, Fisher exact test, frequency, and percentage. Results: More than half (54%) of the nurses were within the age group of 25-34 years. 62% of the nurses graduated from the college of nursing, 58% of the nurses were female, and the majority (88%) of the nurses were married. The highest percentage (64%) of the nurses had a good level of knowledge, while the highest percentage (74%) of the nurses had a fair level of quality nursing care. A highly significant association was found between the quality of nursing care with educational level and the duration of the training course. Also, there was a weak positive correlation between the level of nurses' knowledge and the quality of nursing. Conclusion: Based on the study findings of the present study, it was concluded that the